Utility of published skinfold thickness equations for prediction of body composition in very young New Zealand children. Issue 3 (6th April 2020) - Asadi, Sharin; Bloomfield, Frank H.; Alexander, Tanith; McKinlay, Chris J. D.; Rush, Elaine C.; Harding, Jane E.
Abstract: Measurement of body composition is increasingly important in research and clinical settings but is difficult in very young children. Bioelectrical impedance analysis (BIA) and air displacement plethysmography (ADP) are well-established but require specialist equipment so are not always feasible. Our aim was to determine if anthropometry and skinfold thickness measurements can be used as a substitute for BIA or ADP for assessing body composition in very young New Zealand children. We used three multi-ethnic cohorts: 217 children at a mean age of 24·2 months with skinfold and BIA measurements; seventy-nine infants at a mean age of 20·9 weeks and seventy-three infants at a mean age of 16·2 weeks, both with skinfold and ADP measurements. We used Bland–Altman plots to compare fat and fat-free mass calculated using all potentially relevant equations with measurements using BIA or ADP. We also calculated the proportion of children in the same tertile for measured fat or fat-free mass and tertiles (i) calculated using each equation, (ii) each absolute skinfold, and (iii) sum of skinfold thicknesses. We found that even for the best equation for each cohort, the 95 % limits of agreement with standard measures were wide (25–200 % of the mean) and the proportion of children whose standard measures fell in the same tertile as the skinfold estimates was ≤69 %. We conclude that none of the available published skinfold thickness equations provides good prediction of body composition in multi-ethnic cohorts of very young New Zealand children with different birth history and growth patterns.